2011
DOI: 10.5152/akd.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of association between obstructive sleep apnea and coronary risk scores predicted by tomographic coronary calcium scoring in asymptomatic patients

Abstract: ÖZETAmaç: Obstrüktif uyku apnesi sendromu (OSA) solunumla ilgili uyku bozuklukları içinde incelenen ve vücuttaki birçok sistemi ilgilendiren önemli bir sağlık sorunudur. Koroner arter hastalığı için asemptomatik olup, OSA varlığından şüphe edilen hastalar kullanılarak yapılan bu kesitsel gözlem çalışması, obstrüktif uyku apnesi sendromu ile koroner ateroskleroz varlığı ve yaygınlığı arasındaki ilişkiyi doğrudan araştırmak için planlanmıştır. Yöntemler: Çeşitli nedenler ile uyku laboratuvarında uyku testi yapıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
(24 reference statements)
1
10
1
Order By: Relevance
“…Galectin-3 and age were independent predictors of coronary atherosclerosis in OSAS patients. Furthermore, the presence and total number of coronary plaques and AHI score were found to be higher in the OSAS group than in the controls and in the severe OSAS group compared to the moderate and mild OSAS groups, which is consistent with previous studies [16][17][18][19][20]. Galectin-3 plays a pivotal role in the development of fibrosis and tissue remodelling in kidney and heart [6].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Galectin-3 and age were independent predictors of coronary atherosclerosis in OSAS patients. Furthermore, the presence and total number of coronary plaques and AHI score were found to be higher in the OSAS group than in the controls and in the severe OSAS group compared to the moderate and mild OSAS groups, which is consistent with previous studies [16][17][18][19][20]. Galectin-3 plays a pivotal role in the development of fibrosis and tissue remodelling in kidney and heart [6].…”
Section: Discussionsupporting
confidence: 81%
“…In addition, age was found to be a significant predictor of the presence of coronary calcification in this setting. These analyses suggest that the presence of OSAS may contribute to CAD risk of patients in association with its severity; however, association between OSAS and subclinical atherosclerosis seemed to be primarily dependent on age [20]. In our study, we investigated the relation between galectin-3 concentration and coronary atherosclerosis indicated by the presence and burden of coronary plaque detected by CCTA in patients (3) galectin-3 concentrations correlated with the total number of coronary plaques; and (4) galectin-3 and age were independent significant predictors of coronary atherosclerosis in with OSAS.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…To confirm this study, our results showed that the risk of subclinical atherosclerosis was increasing with a sensitivity of 77.8% when AHI > 16 which is an indicator of moderate-to-severe OSAS. Besides, Kepez et al observed that the relationship between the severity of OSAS and the increase in cardiovascular risk was dependent only on the age of patients [23]. On the contrary, our results demonstrate that the level of AHI and advanced age are independently associated with the development of CAC.…”
Section: Discussioncontrasting
confidence: 58%